Rethinking the Role of Local AIDS Commission in HIV Prevention After the National AIDS Commission Dissolved - Lubis, Dinar Saurmauli; Ardrini, DA Mirah; Nijyoti, Nitya; Mantara, Adi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: The Indonesian government established a non-structural government agency, named the Indonesian National AIDS Commission (INAC) in 2006 to coordinate HIV prevention programs. However, in 2016, the INAC was dissolved by the Presidential Decree no 124-year 2016. Aims: This research aims to identify the effects and challenges faced by the AIDS commission at the provincial level after the INAC was dissolved. Methods: This research used a qualitative research approach with data collection methods through Focus Group Discussion (FGD) and in-depth interviews. The number of participants was 18 people, representing the AIDS Commission, governments as well and NGO-based HIV. The data were analyzed thematically and then presented by using a narrative approach. Results: The findings indicated that the duty and role of the Bali Provincial AIDS Commission (BPAC) to coordinate, integrate, and synergize HIV prevention in Bali remain unchanged. However, it is challenging to coordinate AIDS programs at the provincial level due to changes in parent organizations and reduced funding. Conclusion: The findings show that the duty and role of BPAC to coordinate, integrate, and synergize HIV prevention in Bali remain unchanged. However, change in the BPAC structure and funding reduction has an impact on its role as the HIV coordination agency in Bali. Therefore, to enhance its role and function as an HIV program coordinator, BPAC needs to be supported by regulation to support the bureaucratic independence of BPAC, to innovate, and to obtain other sources of financial/funding support apart from local government.